Portrayal of Difficult Topics in Indonesian Crossover Picturebook's Illustrations - Refita Ika Indrayati (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
Over the past decade, Indonesian picturebook industry has experienced rapid growth, offering an increasingly diverse range of topics for young readers. This diversity has given rise to a new genre of children’s books known as crossover picturebook, which are inclusive narrative form that transcends age limits. This reasearch sought to understand how difficult topics for children are portrayed in this new genre of picturebook. Forty-eight samples of picturebook which contains cross-generational aspects were taken from different categories, including government, non-profit organizations involved in children's education in Indonesia, and award-winning commercial books. All of these samples covered challenging subjects such as cultural differences, disabilities, environmental changes, physical and mental health, death, and social issues. The findings revealed that difficult topics are illustrated using Metaphors and layout compositions such as characters, settings, and activities that divert readers from challenging subjects are strategies employed by illustrator to soften images.Penggambaran Topik Sulit dalam Ilustrasi Buku Anak Lintas-Generasi di Indonesia Abstrak Industri buku cerita anak Indonesia terus mengalami perkembangan yang pesat dalam satu dekade terakhir. Topik-topik yang ditawarkan juga semakin beragam, mulai dari yang cukup mudah hingga yang kompleks. Keberagaman topik ini memunculkan satu genre buku anak baru yaitu buku anak lintas generasi yang merupakan media anak inklusif yang menembus batas umur pembacanya. Penelitian ini berusaha untuk mengungkap bagaimana topik sulit untuk anak diilustrasikan dalam media buku cerita lintas generasi di Indonesia. Sampel ilustrasi diambil dari 48 buku cerita anak dari tiga kategori penerbit; pemerintah, organisasi nirlaba yang bergerak dalam edukasi anak, dan buku komersial yang memenangkan penghargaan. Seluruh sampel buku mengandung muatan topik sulit spesifik seperti perbedaan kultur, disabilitas, perubahan lingkungan hidup, kesehatan jasmani dan rohani, kematian serta isu sosial. Temuan dari analisis mengindikasikan ilustrator Indonesia masih menggunakan pendekatan tidak langsung ketika menggambarkan adegan dengan topik sulit. Adanya penghalusan ilustrasi dengan cara metafora dan komposisi objek seperti penempatan karakter, aktivitas, dan setting membantu mendistraksi pembaca saat menjabarkan topik sulit.